PEMODELAN BANGKITAN PERJALANAN KERJA RUMAH TANGGA BERDASARKAN KARAKTERISTIK SOSIAL EKONOMI DAN AKSES TRANSPORTASI MENGGUNAKAN PENDEKATAN REGRESI LOGISTIK - Putri Balqis (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
Urban transportation demand is strongly influenced by household socioeconomic characteristics and accessibility to transportation infrastructure. Understanding the determinants of work trip generation is essential for urban transport planning and policy formulation. This study aims to model household work trip generation based on socioeconomic characteristics and transportation accessibility using a logistic regression approach. Data were collected through a household questionnaire survey conducted in urban residential areas with 320 respondents. The variables analyzed include household income, number of family members, number of working household members, vehicle ownership, and accessibility to public transportation. Logistic regression analysis was used to estimate the probability of households generating higher work trips. The results indicate that household income, number of working members, vehicle ownership, and accessibility to public transportation significantly influence work trip generation. Households with higher income and better transport accessibility tend to generate more work trips. The model achieved a Nagelkerke R² value of 0.41, indicating a moderate explanatory capability. The developed model can support travel demand forecasting and provide useful insights for transportation planning policies in urban areas. Keywords: Household Travel Demand, Logistic Regression, Socioeconomic Factors, Transport Accessibility, Trip Generation.